Implementation Of Teams Games Tournament Learning Model Using Snakes And Ladders Media To Improve Learning Activities And Outcomes - Fitri, Euis Nessia; Andrian, Deni Dwi (Jurnal Multidisiplin Sahombu, 2024)
The objectives of this research are to describe the learning outcomes of students using the Teams Games Tournament method with the Snakes and Ladders media, and describe the learning activities of students using the Teams Games Tournament method with the Snakes and Ladders media. This research employs a qualitative approach with classroom action research. Data collection techniques were conducted through observation. The findings of this study indicate that the application of the Teams Games Tournament method using the Snakes and Ladders media has a positive impact on improving student learning outcomes, as evidenced by 32 out of 40 students, or 82.50%, achieving the minimum score. This positive increase in activity occurred after implementing the cooperative learning method Teams Games Tournament using the Snakes and Ladders media.